Intellectual Capital Performance and Firm Value: The Effect of MFRS 139 - Rabaya, Abdullah Jihad Rasmi; Saleh, Norman Mohd; Hamzah, Noradiva (The South East Asian Journal of Management, 2020)
Research Aims: We examine the intellectual capital (IC) performance and its connection with firm value. We also investigate whether the adoption of an enhanced quality standard MFRS 139 that affect recognition and measurement of financial instrument's fair values, moderates the relationship between IC performance and firm value. Design/methodology/approach: We used panel data analysis of listed financial institutions' data for 2005 - 2015 period. Research Findings: A positive association between IC performance and firm value is found, proposing that IC is an important resource for firms. The results also show that MFRS 139 implementation strengthens the relationship between IC performance and firm value. This result proposes that the MFRS 139 adoption that reflects enhanced transparency could help investors in assessing firm value. Theoretical Contribution/Originality: This study introduces the effect of information asymmetry on the relation between resources (IC performance) and outcome (firm value) as described in the resources-based view. Thus far, not much is understood on the relationship between IC performance and firm value when transparency is enhanced by a new standard i.e. MFRS 139 adoption. Managerial Implication in the South East Asian context: MFRS 139 adoption enhances managerial decision-making and control. The outcome suggests that mandatory adoption of MFRS 139 facilitates managers and investors to know the real value created by the firm and influence its share price. Research limitation & implications: The conclusion is limited to financial sector in Malaysia that experienced changes in the financial instruments standards.